If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -68 + 3x = 10 Solving -68 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '68' to each side of the equation. -68 + 68 + 3x = 10 + 68 Combine like terms: -68 + 68 = 0 0 + 3x = 10 + 68 3x = 10 + 68 Combine like terms: 10 + 68 = 78 3x = 78 Divide each side by '3'. x = 26 Simplifying x = 26
| 4x+2x^2+60=0 | | (6x-24)(4x-1)-3x(6x-24)=0 | | 3xy+4x=24 | | log9(3x-4)1/2 | | 610x(1-18x)=0 | | -g(x)=9x^2 | | 7x-20=5x+10 | | 4y+-4y+6=6 | | X=6-1.2y | | 50-8=3x | | -4x-3x+6=-20 | | cos((pi*x)/2)=0 | | px^2+qx=0 | | 2x^2+16x+60=-12x | | 5x+5-2x=7 | | 24+4x+y=28+z+8y | | .5x+45=5 | | 2b-6-7b=b+3 | | 3x+4(4x-3)=22 | | 0=3h^2-16h+16 | | 3-4(2x-9)=15 | | 900/(6(5^(1/2)) | | 4y-16y+68=-12 | | x+275x=4275 | | 8=1-4x | | 3+4*2.5-0.5= | | 9n+18= | | -6x+9+8x=-6 | | X+(x*.0925)=1.50 | | (2x+4)(x+1)=0 | | 2(x+8)=4(x-3) | | ln(5)+ln(x)-ln(x+1)=ln(2) |